Analisis Modalitas Pada Cerpen Isshunboushi - Nabila, Femiga Salsa; Wahyuni, Santi; Putri, Tania Luksiana; Kintansari, Tiara Desi; Kintansari, Tiara Desi (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 2 (2021), 2021)
Linguistics studies language as a means of communication. Communication is not limited to verbal speech but also written ones, such as remarks available in short stories. This means that modalities in a short story can be a valid object to be researched. Modality is a marker that expresses a speaker's attitude towards a proposition as well as towards an interlocutor. This research aims to determine modalities used in the short story of Issunboushi. Data is gathered by library research technique, meanwhile analysis method used is qualitative descriptive by observation and note-taking technique. As a result, there are 7 types of modality that can be found, such as irai, ishi, setsumei, meirei, ganbou, hikyou, and gaigen. These modalities' usage are related to context and settings presented in the story.